2021
DOI: 10.21608/tsnj.2021.196635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Toxic Leadership on Intensive Care Units Staff Nurses’ Emotional Intelligence and Their Organizational Citizenship Behaviors

Abstract: Background, toxic leadership becomes a common reality in many organizations. It can cause harm not only to the followers but to the whole organization, results in adverse negative consequences such as decreased motivation, productivity and cooperation which consequently effect on their emotional intelligence and organizational citizenship behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…The present finding was in same line with study done by (Abdallah and Mostafa, 2021), in Egypt, at Tanta city, concluded that the staff nurses at international teaching Hospital perceived that their leaders had low toxic leadership level. Further, Abd El-Aziz Zaki and Elsaiad, (2021) found that, slightly more than three-fifth of nurses perceived a low level of toxic Leadership.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present finding was in same line with study done by (Abdallah and Mostafa, 2021), in Egypt, at Tanta city, concluded that the staff nurses at international teaching Hospital perceived that their leaders had low toxic leadership level. Further, Abd El-Aziz Zaki and Elsaiad, (2021) found that, slightly more than three-fifth of nurses perceived a low level of toxic Leadership.…”
Section: Discussionsupporting
confidence: 93%
“…This explanation was incongruent with a study done by (Abdallah and Mostafa, 2021), in Egypt, at Tanta city, revealed that the staff nurses at General Hospital perceived that their leaders had high levels of toxic leadership. additionally, disagreement with Webster, Brough, & Daly, (2020), who found that overall, toxic leadership behaviors in nurse managers were strongly associated with increased nurse-reported adverse events including reports of complaints and verbal mistreatment from patients and their families, patient falls, health care associated infections and errors in administering and with decreased quality of care.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This is in line with the results of this study, in which authoritarian leadership had the highest mean score. Similarly to our study results, Aasland et al (2010), Abdallah and Mostafa (2021), Abou Ramdan and Eid (2020), Örgev and Demir (2019), and Uysal (2019) found a moderate percentage of toxic leadership in their studies. In comparison, other studies by Kusy and Holloway (2009) and Sezici (2016) have reported that participants perceived high levels of toxic leadership in their workplaces.…”
Section: Discussionsupporting
confidence: 90%
“…Two studies reported a significant increase in silence behavior in nurses who perceived their nurse managers as toxic (Abdelaliem and Abou Zeid, 2023; Reyhanoglu and Akin, 2022). Other studies associated toxic leadership by nurse managers with reduced emotional intelligence (Abdallah and Mostafa, 2021) and increased use of conflict management styles such as avoiding, accommodating, competing and collaborating (Abou Ramadan and Eid, 2020). Toxic leadership had no significant effects on nurses’ professional values, as reported in one study (Özkan et al , 2022).…”
Section: Major Findingsmentioning
confidence: 99%